Optimizing the role of stakeholders in the development of hexa-helix-based craft sector MSMEs to increase sustainable competitive advantage - Karsinah, Karsinah; Santosa, Purbayu Budi; Iskandar, Deden Dinar (Edelweiss Applied Science and Technology, 2025)
This study aims to develop a model for optimizing the role of stakeholders in the development of the local wisdom-based craft sector of UMKM in order to increase sustainable competitive advantage in Central Java. This study uses a mixed methods approach. The data used are primary data obtained from key persons selected using purposive sampling techniques. Data collection was conducted through Focus Group Discussions (FGD) and questionnaires. The analysis method used in this study employs Mactor analysis (Matrix of Alliances and Conflicts Tactics, Objectives, and Recommendations). The research results show that the stakeholders who have the strongest influence in the development of MSMEs in the craft sector are investors, the Cooperatives and UMKM Office, and also Academics. Stakeholders with the highest competitiveness include investors, the Cooperatives and UMKM Office, Academics, and the Industry and Trade Office. The results of the analysis also show that all stakeholders support all the objectives that have been set; this is indicated by the fact that all the objective maps show yellow, which means all stakeholders support/agree with all objectives. The stakeholder groups of banking, UMKM actors, mass media, investors, and the Cooperatives and UMKM Office are groups that can form a very strong alliance for the success of developing UMKM in the craft sector. The Industry and Trade Office and the mass media have the strongest role in implementing the program to increase export promotion of craft products. Furthermore, banking has the strongest role in implementing the program to provide access to capital for Craft UMKM. Additionally, the Cooperatives and UMKM Office has the strongest role in implementing the UMKM education and training program, as well as the craft center and UMKM cluster development program. This research has limitations in the form of research objects that only focus on MSMEs in the craft sector, so further research can expand research objects beyond crafts.